PENGEMBANGAN BAHAN AJAR E-LKPD BERBANTUAN SIGIL PADA MATA PELAJARAN AKUNTANSI LEMBAGA/INSTANSI PEMERINTAH DI SMK NEGERI 2 BUDURAN - Iswianti, Idha Rahma; Pratiwi, Vivi (EDUNOMIA: Jurnal Ilmiah Pendidikan Ekonomi, 2024)
Teaching materials in the Independent Curriculum require interesting innovations and utilize technology, information and digital forms of communication in the process of teaching and learning activities. This research aims to develop E-LKPD and analyze the feasibility and response of students to the Sigil-Assisted E-LKPD in Accounting Subjects for Government Institutions/Agencies at SMK Negeri 2 Buduran which has been developed. This type of research is Research and Development (R&D) using the Thiagarajan 4-D development model which consists of 4 stages including the definition stage, design, development, and dissemination. The research subjects were 20 students of class XI AKL at SMK Negeri 2 Buduran Sidoarjo. Data collection techniques use study sheets, validation sheets, and student response questionnaires. The data obtained were analyzed descriptively using the percentage technique. The results of this research indicate that the feasibility of e-LKPD assisted by Sigil is very feasible with an average percentage of 94.2% including assessment of the components of content aspects, presentation aspects, linguistic aspects and graphic aspects. The students' response to e-LKPD assisted by Sigil was very understanding with an average percentage of 99%. It can be concluded that the Sigil-assisted E-LKPD in the Government Institution/Agency Accounting Subject at SMK Negeri 2 Buduran is very suitable for use as teaching material.